Cancer theragnostics: closing the loop for advanced personalized cancer treatment through the platform integration of therapeutics and diagnostics - Sergeeva, Olga V.; Luo, Liang; Guiseppi-Elie, Anthony (Frontiers in Bioengineering and Biotechnology, 2025)
Cancer continues to be one of the leading causes of death worldwide, and conventional cancer therapies such as chemotherapy, radiation therapy, and surgery have limitations. RNA therapy and cancer vaccines hold considerable promise as an alternative to conventional therapies for their ability to enable personalized therapy with improved efficacy and reduced side effects. The principal approach of cancer vaccines is to induce a specific immune response against cancer cells. However, a major challenge in cancer immunotherapy is to predict which patients will respond to treatment and to monitor the efficacy of the vaccine during treatment. Theragnostics, an integration of diagnostic and therapeutic capabilities into a single hybrid platform system, has the potential to address these challenges by enabling real-time monitoring of treatment response while allowing endogenously controlled personalized treatment adjustments. In this article, we review the current state-of-the-art in theragnostics for cancer vaccines and RNA therapy, including imaging agents, biomarkers, and other diagnostic tools relevant to cancer, and their application in cancer therapy development and personalization. We also discuss the opportunities and challenges for further development and clinical translation of theragnostics in cancer vaccines.